2002
DOI: 10.2176/nmc.42.53
|View full text |Cite
|
Sign up to set email alerts
|

Etizolam, an Anti-anxiety Agent, Attenuates Recurrence of Chronic Subdural Hematoma. Evaluation by Computed Tomography.

Abstract: Etizolam, an anti-anxiety agent which is an antagonist of platelet-activating factor receptors, was administered to patients with chronic subdural hematoma (CSH) after hematoma removal to assess the effectiveness for preventing recurrence compared with control patients not given the drug after surgery. The remaining volumes of subdural hematomas on brain computed tomography were measured approximately 1 month after removal. Volume in the etizolam group (15 patients) was significantly smaller than in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…Our previous preliminary study revealed that administration of etizolam attenuated recurrence after surgery for CSDH, and that the remaining volume of hematoma 1 month after sur-gery was significantly smaller in the etizolam group than in the control group. 9) In the present study, etizolam administration and low density of hematoma on CT were found to be independent predictors for resolution without surgery, whereas hemiparesis as an initial symptom was an independent predictor for requirement for surgery. The initial symptoms of spontaneous resolution of CSDH are usually described as mild, such as headache and decrease in cognitive level.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Our previous preliminary study revealed that administration of etizolam attenuated recurrence after surgery for CSDH, and that the remaining volume of hematoma 1 month after sur-gery was significantly smaller in the etizolam group than in the control group. 9) In the present study, etizolam administration and low density of hematoma on CT were found to be independent predictors for resolution without surgery, whereas hemiparesis as an initial symptom was an independent predictor for requirement for surgery. The initial symptoms of spontaneous resolution of CSDH are usually described as mild, such as headache and decrease in cognitive level.…”
Section: Discussionsupporting
confidence: 47%
“…7,8) Our recent prospective study showed that etizolam, a PAF receptor antagonist, attenuates the recurrence of CSDH after hematoma evacuation and irrigation. 9) The present study examined whether oral administration of etizolam decreased the requirement for surgery and identified the predictive factors.…”
Section: Introductionmentioning
confidence: 99%
“…CV 3988 partially rescues neurons from PAFR-dependent apoptosis resulting from C 18 -PAF signal transduction, consistent with its PAFR specificity; however, CV 3988 has no impact on PAF signaling in the absence of PAFR, regardless of the PAF isoform present. These data may help explain the mixed success of single PAF antagonists in therapeutic intervention (43)(44)(45)(46)(47)(48). We were surprised to see that PAFR antagonism had no impact on the survival of PAFR 1/1 neurons treated with C 16 -PAF, inasmuch as we have previously reported pro-apoptotic activity in nonneuronal PC12 cells (18).…”
Section: Discussionmentioning
confidence: 73%
“…Рекомендаций по лечению резидуальных ХСГ в научной литературе мы не нашли. Опубликованы результаты исследований применения пероральных препаратов (транексамовой кислоты [3], периндоприла [4], этизолама [5], аторвастатина [6], стрептокиназы-стрептодорназы [7]), парентерального введения стероидных гормонов [8], гипергидратации [1] обСуждение Первые сообщения о лечении рецидивных ХСГ путем эмболизации средней оболочечной артерии относятся к 2013 г. [9].…”
Section: Russian Journal Of Neurosurgeryunclassified